(untitled) (Avocetta, 2017)
The Golden Eagle Aquila chrysaetos has been regarded as one of the most representative breeding bird species in the province of Trento, and has been the focus of several research projects since the 1980s (Pedrini 1992, Pedrini & Sergio 2001a, 2002), as well as several conservation initiatives (P.A.T. 2011, LIFE11/NAT/IT/000187 “TEN” Trentino ecological Network; www.lifeten.tn.it). The Golden Eagle is classified as “vulnerable” in the Red List of birds breeding in Trentino (Pedrini et al. 2005). Its conservation status, coupled with the importance of this species for the Trento province, promoted research projects in the past (Sergio et al. 2006) and also monitoring activities in several protected areas in Trentino (Adamello Brenta Park, Stelvio National Park) and in other pre-alpine mountain areas (carried out by Muse, formerly Museo Tridentino di Scienze Naturali). This paper provides an update of the conservation status of this species in Trentino, on the basis of the ongoing monitoring activities, and compares it with the status of this species at the national level, which is considered “inadequate” mostly because of the reduction of high-altitude grasslands (Gustin et al. 2016).